The diagnostic value of global longitudinal strain on doxorubicin-induced cardiotoxicity in pediatric cancer patients: a cross-sectional study - Lesmanawati, Dyah Ayu Shinta; Hilmanto, Dany; Sari, Nur Melani; Hakim, Dzulfikar D. L.; Rahayuningsih, Sri Endah; Susanah, Susi (Frontiers in Pediatrics, 2025)
BackgroundChemotherapy is a critical modality in the treatment of pediatric cancer. However, the risk of adverse effects remains a significant challenge despite the considerable advancements in chemotherapy efficacy. Anthracyclines are a cornerstone in the treatment of various childhood cancers but are associated with a notable risk of cardiotoxicity. Early detection of cardiac dysfunction in pediatric cancer patients is vital to prevent progression to heart failure, with echocardiography being one of the primary modalities for such assessments. Speckle Tracking Echocardiography (STE) is a recommended method for the early detection of cardiotoxicity in adult cancer patients, although its application in the pediatric population remains limited. This study aims to assess the diagnostic value of global longitudinal strain (GLS) in detecting doxorubicin-induced cardiotoxicity in pediatric cancer patients and to examine its correlation with cumulative doxorubicin doses.MethodsThis cross-sectional study involved 52 pediatric cancer patients at Dr. Hasan Sadikin General Hospital. We performed both conventional echocardiography and STE for those receiving doxorubicin as their chemotherapy regimen. STE evaluated the correlation between cumulative doxorubicin dose and left ventricular function. Receiver Operating Characteristic (ROC) and area under the curve (AUC) were performed to evaluate the predictive model of GLS in diagnosing cardiac dysfunction based on conventional methods. This analysis also measures the model of cumulative doxorubicin doses to predict reduced GLS percentages.ResultsA total of 52 subjects (67.3% male, mean age 10.3 years) were included in this study. Conventional echocardiography detected systolic dysfunction in 21.2% and diastolic dysfunction in 23.1% of patients. GLS measurements identified ventricular dysfunction in 19.2% of subjects. Significant risk factors for cardiotoxicity were cancer type and nutritional status, with p-values of 0.006 and 0.028, respectively. GLS scores were significantly lower in patients with low systolic function (18.3%) compared to those with normal function (−23.6%), with a mean difference of 5.3% (p < 0.0001), and a similar difference was found for diastolic dysfunction. ROC curve analysis revealed an area under the curve (AUC) of 0.793 for systolic dysfunction and 0.746 for diastolic dysfunction, with cutoff values of −19.10 for systolic (72.7% sensitivity, 65.4% specificity) and −19.55 for diastolic dysfunction (58.3% sensitivity, 87.5% specificity).ConclusionThis study suggests that GLS derived from STE may help identify early alterations in left ventricular function in pediatric patients receiving doxorubicin. Although reduced GLS was associated with systolic and diastolic dysfunction, differences were modest and within physiological limits. These findings highlight the potential role of GLS in cardiac monitoring, though further research is needed to confirm its diagnostic value.